Pattern Recognition and Feedforward Neural Networks - Bishop, Christopher (MIT Press, 1999)
A feed-forward network can be viewed as a graphical representation of parametric function which takes a set of input values and maps them to a corresponding set of output values (Bishop, 1995). Figure 1 shows an example of a feed-forward network of a kind that is widely used in practical applications.
The MIT Encyclopedia of the Cognitive Sciences